Peran Inti Muda Papua terhadap Pendampingan Penularan HIV/AIDS pada Remaja - Nasrianti, Nasrianti; Watunglawar, Crystin E; Patungo, Viertianingsih; Hasnia, Hasnia (Journal of Telenursing (JOTING), 2023)
This research aims to explore the role of Inti Muda Papua in preventing the transmission of HIV/AIDS to adolescents in Jayapura Regency. The method used is qualitative research with an exploratory phenomenology approach. The results of the study found four themes of facilities provided by the Papuan Youth Core organization to teenagers with HIV/AIDS, Monitoring and Evaluation Program in HIV/AIDS prevention, Experiences of members of the Papuan Youth Core organization, the role of the Papuan Youth Core organization is expected to be carried out by developing programs that structured in terms of reducing the spread of the HIV/AIDS virus by organizing and collaborating with other organizations throughout the world that are involved in reducing the spread of HIV/AIDS. In conclusion, the actions given by the organization to teenagers infected with HIV/AIDS and teenagers who are not infected are through the dissemination of information, apart from programs arranged by health services in undergoing treatment programs as well as support from the family and the surrounding environment. Keywords: HIV/AIDS, Mentoring, Adolescents